2000
DOI: 10.1007/pl00007285
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar gliomas in children with NF1: pathology and surgery

Abstract: Cerebellar gliomas associated with NF1 (CGNF1) are rarely reported in the literature, and they are considered to be malignant in a high proportion of cases. In an attempt to improve the definition of this disease and clarify its management, we reviewed our patients with CGNF1 and compared their tumors with sporadic cerebellar gliomas (SGC). We operated on six children with CGNF1, all but one of whom were asymptomatic. They represented one-tenth of all pediatric cerebellar gliomas, and one third of NF1-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The radiological findings must be interpreted in conjunction with clinical findings. Cerebellar tumors appear to have a particularly poor prognosis in NF I. Vinchon et al suggested that surgical treatment of gliomas in NF I is safe, especially with the help of neuronavigation for location of these small, deep lesions [14].…”
Section: Brain Gliomasmentioning
confidence: 99%
“…The radiological findings must be interpreted in conjunction with clinical findings. Cerebellar tumors appear to have a particularly poor prognosis in NF I. Vinchon et al suggested that surgical treatment of gliomas in NF I is safe, especially with the help of neuronavigation for location of these small, deep lesions [14].…”
Section: Brain Gliomasmentioning
confidence: 99%
“…Brain tumors usually follow a less aggressive course in people with NF1 than in other individuals. 22,23,29,30 Malignant peripheral nerve sheath tumors are the most frequent malignant neoplasms associated with NF1, occurring sometime in the life of ϳ10% of affected individuals. 6,[31][32][33][34] These malignancies tend to develop at a much younger age and have a poorer prognosis for survival in people with NF1 than in the general population.…”
Section: Other Neoplasmsmentioning
confidence: 99%
“…20,211 The less aggressive course of most brainstem and cerebellar gliomas in people with NF1 should be taken into consideration in the management of these tumors. 22,23,29,30 Bracing is usually ineffective in children with NF1 and rapidly progressive dystrophic scoliosis. Treatment requires surgery, which may be complex and difficult.…”
Section: Treatment Of Disease Manifestationsmentioning
confidence: 99%
“…Neurofibromatosis 1 (NF1) is caused by mutations within the neurofibromin gene located on chromosome 17q. In up to 15% of cases NF1 is associated with LGG of the optic tract and hypothalamus [101,102]. This suggests a role for NF1 or its signal transduction pathway (the mitogen-activated protein kinase (MAPK) pathway) in the development of sporadic JPA through ras inhibition, but this has not been proven.…”
Section: Paediatric Gliomasmentioning
confidence: 99%